1997
DOI: 10.1111/j.1349-7006.1997.tb00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Effect of Polyethylene Glycol–modified Fullerene on Tumor

Abstract: Fullerene (Cm) efficiently generates singlet oxygen when irradiated with light, and thus should have a photodynamic effect on tumors, if it is accumulated in the tumor tissue. To explore tumor targeting of CU, we chemically modified the water–insoluble C60 with polyethylene glycol (PEG), not only to make it soluble in water, but also to enlarge its molecular size. When injected intravenously into mice carrying a tumor mass in the hack sulicutis, the C60–PEG conjugate exhibited higher accumulation and more prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
122
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(124 citation statements)
references
References 22 publications
1
122
0
1
Order By: Relevance
“…Fullerene molecules, the third form of pure carbon in addition to the diamond and graphite forms, have attracted much attention to their biomedical applications (17). It has been demonstrated that fullerenes can generate singlet oxygen and suppress tumor growth without damage to normal skin of the mice exposed to visible light (18). We have found that metallofullerene nanoparticles penetrate plasma membrane of tumor cells and result, to some degree, in shrinkage of solid tumors in vivo (19,20).…”
mentioning
confidence: 92%
“…Fullerene molecules, the third form of pure carbon in addition to the diamond and graphite forms, have attracted much attention to their biomedical applications (17). It has been demonstrated that fullerenes can generate singlet oxygen and suppress tumor growth without damage to normal skin of the mice exposed to visible light (18). We have found that metallofullerene nanoparticles penetrate plasma membrane of tumor cells and result, to some degree, in shrinkage of solid tumors in vivo (19,20).…”
mentioning
confidence: 92%
“…The presence of sp 3 hybridized carbons at d ¼ 94 ppm indicated that products 1aN3SF-1cN3SF and 2aN3SF-2cN3SF possessed a [6,6]-closed structure. The absence of sp 3 hybridized C 60 resonances at d > 84 in the 13 C NMR spectra of series 1aNSF-1cNSF and series 2aNSF-2cNSF accounted for an open [5,6]-azabridged structure.…”
Section: Resultsmentioning
confidence: 99%
“…It is a thermogellable polysaccharide consisting of (b-1,3)-linked glucose residues, which can be subjected to partial sulfonation or persulfonation to yield soluble curdlan sulfate with specific biological activities. There are two main reasons that curdlan sulfate is of particular interest for fullerene chemistry: (1) depending on the degree of substitution, a series of C 60 -substituted curdlan sulfates with adequate water solubility for prospective photodynamic therapeutic agents [5][6][7][8] can be prepared, and (2) curdlan sulfates exhibit strong anti-HIV activity (EC 50 ¼ 0.04-3.08 lg mL À1 ) 9 and can act as delivery carriers of cationic-fullerene-based AIDS drugs 10 to the lymphoid tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Tabata et al reported (44) in 1997 that a C 60 -PEG conjugate injected intravenously into mice carrying a subcutaneous tumor followed by exposure of the tumor site to visible light exhibited a stronger suppressive effect than Photofrin. Liu et al (45) prepared C 60 -PEG attached to DTPA-Gd and carried PDT out MRI imaging and PDT of subcutaneous tumor s using 500-500-nm light.…”
Section: Discussionmentioning
confidence: 99%